2016
DOI: 10.1523/jneurosci.4130-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein Protects Neuronal Network Function after Hypoxia via Control of Voltage-Gated Calcium Channels

Abstract: Acute cerebral ischemia and chronic neurovascular diseases share various common mechanisms with neurodegenerative diseases, such as disturbed cellular calcium and energy homeostasis and accumulation of toxic metabolites. A link between these conditions may be constituted by amyloid precursor protein (APP), which plays a pivotal role in the pathogenesis of AlzheimerЈs disease, but has also been associated with the response to acute hypoxia and regulation of calcium homeostasis. We therefore studied hypoxia-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
3
40
0
Order By: Relevance
“…The cleavage and shedding of the luminal, or ecto, domain of APP by the metalloprotease ␣-secretase is a key processing event, as it is considered to minimize the generation of the pathogenic A␤ peptides associated with Alzheimer's disease (38,39). In addition, soluble sAPP␣ is known to have neurotrophic (40) and neuroprotective (41)(42)(43) properties. APP cleavage by membrane-bound ␣-secretase can occur at the plasma membrane (13,44); however, other cellular location(s) of ␣-secretase cleavage remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage and shedding of the luminal, or ecto, domain of APP by the metalloprotease ␣-secretase is a key processing event, as it is considered to minimize the generation of the pathogenic A␤ peptides associated with Alzheimer's disease (38,39). In addition, soluble sAPP␣ is known to have neurotrophic (40) and neuroprotective (41)(42)(43) properties. APP cleavage by membrane-bound ␣-secretase can occur at the plasma membrane (13,44); however, other cellular location(s) of ␣-secretase cleavage remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…In the alternative, non-amyloidogenic pathway cleavage of APP within the Ab region by the major a-secretase ADAM10 (a disintegrin and metalloprotease) prevents Ab generation and liberates APPsa that is secreted into the extracellular space (Saftig & Lichtenthaler, 2015). While our previous studies and work from others indicated that APPsa has neurotrophic and neuroprotective effects, including synaptogenic, LTP facilitating and memory enhancing properties (Meziane et al, 1998;Ring et al, 2007;Taylor et al, 2008;Milosch et al, 2014;Weyer et al, 2014;Hick et al, 2015;Hefter et al, 2016;Plummer et al, 2016), only few and mostly conflicting studies have as yet addressed the functions of APPsb (Nikolaev et al, 2009;Li et al, 2010;Weyer et al, 2011;Chasseigneaux & Allinquant, 2012). An important and still unresolved question is whether in addition to neurotoxic Ab accumulation a concomitant reduction in APPsa level, or an altered APPsa/APPsb ratio may contribute to AD symptoms and pathogenesis (reviewed by Mockett et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…In this regard, it will be crucial to know whether APPsa and APPsb, that is only 16 amino acids shorter than APPsa, serve largely similar or distinct, possibly even opposite physiological functions. While our previous studies and work from others indicated that APPsa has neurotrophic and neuroprotective effects, including synaptogenic, LTP facilitating and memory enhancing properties (Meziane et al, 1998;Ring et al, 2007;Taylor et al, 2008;Milosch et al, 2014;Weyer et al, 2014;Hick et al, 2015;Hefter et al, 2016;Plummer et al, 2016), only few and mostly conflicting studies have as yet addressed the functions of APPsb (Nikolaev et al, 2009;Li et al, 2010;Weyer et al, 2011;Chasseigneaux & Allinquant, 2012). So far, the molecular basis of any difference compared to APPsa remained unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Investigations by Yang et al (2009) yielded that deletion of APP in hippocampal neurons increased L-type voltage gated Ca 2+ channel (LTCC) levels and function underlying an altered GABAergic STP. Likewise, a recent report implied APP possibly via the APPsα fragment to stabilize Ca 2+ homeostasis by regulating inhibition of LTCCs (Hefter et al, 2016). Nevertheless, APLP1 deficiency causes no LTP deficit even though GABAergic inhibition is affected in APLP1-KO mice.…”
Section: Role Of the App Protein Family In Synaptic Inhibitionmentioning
confidence: 98%